Sistem Informasi Data Nilai Siswa Pada Sekolah Menengah Kejuruan Negeri 03 Empat Lawang Sumatera Selatan - Meta Ulandari; Asnawati Asnawati; Ricky Zulfiandry (UNIVED Press, 2025)
SMK Negeri 03 Empat Lawang of South Sumatra is an agency that operates in the field of education, the objective that must be observed SMK Negeri 03 Empat Lawang of South Sumatra is the process of processing student value data, the procedures that occur in processing student value data are still manual or written, the values students and lecturers are collected in a large number of papers and it makes it difficult for teachers, admins to control them, the problems that occur include quite a few test papers, assignments, final semester exams being lost, students also have to wait a long time to find out their grades, therefore in this final assignment discusses the PHP MYSQL-based student grade data information system at SMK Negeri 03 Empat Lawang of South Sumatra. The software development method used is Waterfall, and in the research process the data collection techniques used include interview observation and literature study, this grade data information system designed to simplify the way teachers and admins work in managing student grade data such as per meter report cards, apart from that, students can also view and print their own report cards online.